Continuing Engineering Education and Sustainability: IACEE Contribution with SERINA and Porto Declaration - Alfredo Soeiro (2018)
In the IACEE (International Association for Continuing Engineering Education - www.iacee.org) world conference of 2016 a declaration was signed by participants. IACEE is an international organization dedicated to the Continuing Professional Development (CPD) and to the Continuing Education in Engineering (CEE). IACEE recognizes the scale and complexity of the gap between existing solutions and the needs facing our planet concerning sustainability and that the IACEE is uniquely placed to act on this opportunity. IACEE seeks to pivot the organization to connect individuals, universities, industry, government and NGO organizations to meet the grand challenges facing humanity and the world. Keeping with its dedication to lifelong learning, IACEE has developed and will continue to develop global initiatives to address those twenty-one century challenges threatening the survival of human kind through collaboration, design, creative thinking and engineering. Continuing Engineering Education (CEE) can provide training for engineers that are active with immediate impact on sustainability. Change and improvement of active engineers can be obtained mostly by education and training of the current engineering community around the world. The role of online learning is crucial to change habits of engineers and improve the sustainability component of decisions. The strategic initiative SERINA is presented with future plans to improve the sustainable performance of engineers through training.